2020
DOI: 10.1002/anie.202008035
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genome Mining Reveals a Class V Lanthipeptide Containing a d‐Amino Acid Introduced by an F420H2‐Dependent Reductase

Abstract: Lantibiotics are a type of ribosomally synthesized and post‐translationally modified peptides (termed lanthipeptides) with often potent antimicrobial activity. Herein, we report the discovery of a new lantibiotic, lexapeptide, using the library expression analysis system (LEXAS) approach. Lexapeptide has rare structural modifications, including N‐terminal (N,N)‐dimethyl phenylalanine, C‐terminal (2‐aminovinyl)‐3‐methyl‐cysteine, and d‐Ala. The characteristic lanthionine moiety in lexapeptide is formed by three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(118 citation statements)
references
References 30 publications
3
114
1
Order By: Relevance
“…In 2013, a new and still commonly accepted classification was introduced based on the characteristics of the modification enzymes [1]. Recently, a new class was identified, which brings the number of different classes to five [17,18]. In class I, the enzymes needed for the modification are two single monofunctional enzymes where the dehydratase (LanB) and the cyclase (LanC) are forming a complex in the cell.…”
Section: Bacteriocins From Gram-positive Bacteriamentioning
confidence: 99%
“…In 2013, a new and still commonly accepted classification was introduced based on the characteristics of the modification enzymes [1]. Recently, a new class was identified, which brings the number of different classes to five [17,18]. In class I, the enzymes needed for the modification are two single monofunctional enzymes where the dehydratase (LanB) and the cyclase (LanC) are forming a complex in the cell.…”
Section: Bacteriocins From Gram-positive Bacteriamentioning
confidence: 99%
“…Recently, Tao et al identified lexapeptide, a new RiPP containing both Lan and AviCys thioether residues, and the associated biosynthetic gene cluster in S. rochei Sal35. 16 Using a similar heterologous co-expression method in E. coli, four dedicated PTM enzymes, i.e., LxmKYXD, were indicated to be necessary for the formation of the AviCys residue in lexapeptide. Remarkably, despite poor homology in primary sequence, secondary structure prediction revealed that LxmKYXD are the counterparts of TvaCDEFS-87 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The counterparts of TvaFS-87 were known in the biosynthesis of various AviCys-containing RiPPs. Either as a LanD protein (for lanthipeptides [10][11][12]15 ) or as a LanD-like protein (for non-lanthipeptides 6,8,16 ), these flavoproteins share the oxidative decarboxylation activity necessary for AviCys formation and can process the C-terminal Cys residue of a precursor peptide to an enethiol before Michael addition to the upstream Dha/Dhb residue. The homologs of TvaCS-87 and TvaES-87 were previously annotated as hypothetic proteins, with the exception in ref.…”
Section: Identification Of Genes Coding For Avicys Formation In the Tmentioning
confidence: 99%
“…classified based on the biosynthetic mechanisms involved in their structural maturation, the recently discovered modified peptides, including Cocaoidin and Lexapeptide, exhibited novel modification features such as different biosynthetic gene clusters and have been introduced as class V lanthipeptides (Ortiz-López et al, 2020;Xu et al, 2020).…”
Section: Lanthipeptides Are Ribosomally Produced and Post-translationmentioning
confidence: 99%